PENDIDIKAN KARAKTER DI PONDOK PESANTREN: ANALISIS BIBLIOMETRIK BERBASIS GOOGLE SCHOLAR MENGGUNAKAN VOSVIEWER - Zaini Hafidh; Ilham Muhammad Nurjaman; Abdul Baits; Irfan Goffary (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2023)
This study aims to describe and analyze scientific articles on the theme of character education research in Islamic boarding schools. This research analysis uses VosViewer through a bibliometric approach; article references are obtained from the Google Scholar database with the publish or perish application. Character education in Islamic boarding schools is a reference in the search process. Found 996 articles that are considered relevant related topics. The research period used as a document indexed by Google Scholar is from 2019–2022. The results of the study focused on finding and analyzing topics and themes related to character education in Islamic boarding schools and other data analysis. Keywords about character education in Islamic boarding schools are associated with 4 clusters and 189 links, for a total link strength of 1754. The results of the analysis of the development of publications in the 2019–2022 period indicate that research on character education in Islamic boarding schools tends to be popular and has been carried out by many researchers. The highest number of publications in 2022 is 370, and the least is 155. Researchers analyzed published articles about character education in Islamic boarding schools and their relation to problem areas using VosViewer. This study can be a starting point for research related to further research regarding research on Islamic boarding schools and other research developments related to the world of Islamic boarding schools in general.